A possible serologic biomarker for maternal immune activation-associated neurodevelopmental disorders found in the rat models. (December 2016) - Oh-Nishi, Arata; Koga, Kaori; Maeda, Tadakazu; Suhara, Tetsuya
Highlights: MIA model rat's serum proteome analysis showed augmentation of Ig light chain. Augmentation of Ig light chain was also observed in schizophrenia patient's sera. Ig light chain assay of the patients would be worthy to be validated in larger scale. Abstract: Epidemiological studies have shown that maternal infection during early pregnancy increases the risk of neurodevelopmental disorders (i.e., schizophrenia or autism) in offspring. Recently, diagnostic/stratification biomarkers for the maternal immune activation background in patients with neurodevelopmental disorders have been energetically searched for in the patient blood. Here, we report a novel serologic marker candidate for the disorders found in the maternal immune activation (MIA) rat model. Serum proteome analysis of the MIA rat showed that the immunoglobulin (Ig) light chain is reproducibly augmented. The Ig light chain in sera takes two forms — free form or bound to the Ig heavy chain. Only the former is an inflammatory disease marker, but pro-inflammatory cytokine levels in the sera of the MIA rats were below detectable limits of the ELISA protocol we used. We thereby carried out serum assays of Ig light chains and pro-inflammatory cytokines of commercially available schizophrenia patient sera for research. Although the number of samples was limited, we found augmentation of free Ig light chains but not pro-inflammatory cytokines in sporadic schizophrenia patient sera. Our findings suggest that Ig light chain assay of the schizophrenia/autism patient sera would be worthy to be validated in larger scale.